(untitled) (Revista de Ciências Agroveterinárias, 2018)
Considering the scarcity of information regarding blood parameters of Pêga donkeys (Equus asinus), and the influence of factors such as breed and physiological status on these parameters, this study aimed to evaluate the influence of pregnancy on hematological, blood biochemical and serum protein profiles of the Pêga donkey, using samples from 59 female adult donkeys, 22 pregnant and 37 non-pregnant, kept under field conditions. The parameters measured were counts of red blood cells (RBC), white blood cells (WBC), basophils, eosinophils, bands, segmented neutrophils, lymphocytes, monocytes and platelets; and the levels of packed cell volume, hemoglobin concentration, alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase, creatine kinase, gamma-glutamyl transferase, urea, glucose, cholesterol, triglycerides, total calcium, phosphorus, magnesium, chlorides, sodium, potassium, ionized calcium, creatinine, total protein, albumin, total, direct and indirect serum bilirubin. Serum protein fractionation was performed by sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE), which found 10 proteins: immunoglobulins A and G, ceruloplasmin, transferrin, albumin, haptoglobin, α1-acid glycoprotein, 138 kDa (MWP138), 33 kDa (MWP33) and 23 kDa (MWP23) molecular weight proteins. RBC and triglycerides were higher in pregnant females. Urea, Immunoglobulin A, MWP138 and MWP23 concentrations were higher in non-pregnant mares. This study presented differences from previous studies, and some differences in blood variables between pregnant and non-pregnant Pêga donkeys, confirming that pregnancy causes significant metabolic changes, which must be considered in the clinical evaluation of these animals.